Developing an effective adaptive monitoring network to support integra ted coastal management in a multiuser nature reserve - Vugteveen, Pim; Katwijk, Marieke M.; Rouwette, Etiënne; Lenders, H. J. Rob; Hanssen, Lucien (Ecology and Society, 2015)
ABSTRACT. We elaborate the necessary conceptual and strategic elements for developing an effective adaptive monitoring network to support In tegrated Coastal Management (ICM) in a multiuser nature reserve in the Dutch Wadden Sea Region. We discuss quality criteria and enabling act ions essential to accomplish and sustain monitoring excellence to supp ort ICM. The Wadden Sea Long-Term Ecosystem Research project (WaLTER) was initiated to develop an adaptive monitoring network and online dat a portal to better understand and support ICM in the Dutch Wadden Sea Region. Our comprehensive approach integrates ecological and socioecon omic data and links research-driven and policy-driven monitoring for s ystem analysis using indicators of pressures, state, benefits, and res ponses. The approach and concepts we elaborated are transferable to ot her coastal regions to accomplish ICM in complex social-ecological sys tems in which scientists, multisectoral stakeholders, resource manager s, and governmental representatives seek to balance long-term ecologic al, economic, and social objectives within natural limits.
Keywords: IMPORTANT